2012
DOI: 10.1080/10236244.2012.715742
|View full text |Cite
|
Sign up to set email alerts
|

A geospatial analysis of shark attack rates for the east coast of Florida: 1994–2009

Abstract: Shark attacks have historically been studied from a viewpoint of encounter number per region and so limited to the areas in which the attacks occurred. In this exploratory modeling study, the goal was to examine whether an area-specific cluster analysis algorithm undertaken with a modern cluster analysis tool (SaTScan TM 9.1.0) could enhance our spatial and spatio-temporal understanding of attack patterns. The data used were from Florida's east coast between 1994 and 2009. The program suggests several high-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…It is true that surfers are the most exposed group when it comes to contact with sharks [33], but the idea of a mistake, as a cause for bites, is not true [6,7]. We have shown that there is no mistake when a white shark bites a surfer [7].…”
Section: What Is It With Surfers and Sharks?mentioning
confidence: 84%
See 2 more Smart Citations
“…It is true that surfers are the most exposed group when it comes to contact with sharks [33], but the idea of a mistake, as a cause for bites, is not true [6,7]. We have shown that there is no mistake when a white shark bites a surfer [7].…”
Section: What Is It With Surfers and Sharks?mentioning
confidence: 84%
“…The obvious shortcoming of such numbers is that they cannot be easily compared, except for the actual difference since no connection is made to the numbers of people on the beach at the time. To overcome this shortcoming, we defined the term "bite rates," which reflects the ratio between the total annual bites for a certain region to the yearly estimated beach attendance for that region [33]. For our studies, the beach attendance data were taken from the estimates determined by the United States Lifesaving Association (USLA), a not-for-profit association of professional lifeguards.…”
Section: What Do Bite Rates Tell Us?mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been shown [27] that e.g., the incident rate of California likely depends primarily on the migration routes of mature female white sharks, Carcharodon carcharias, hence this reflects a one species effect that does not show up e.g. in Florida where other species are involved in incidents [28].…”
Section: Methodsmentioning
confidence: 99%
“…Surfing incidents were separated because it is known that the highest waves, the best for surfing, occur around the full and new moon, bringing more surfers to the beaches than at other times. Furthermore, it has been shown that surfing carries a higher risk of being bitten than other beach-oriented activities [28,29].…”
Section: Methodsmentioning
confidence: 99%